Penentuan pH dan Waktu Kontak Optimum Penyerapan Ion Zn2+ Pada Silika Modifikasi Sulfonat - Dwi Putri, Vika Trisna; Oktavia, Budhi; Dewata, Indang; Hardeli, Hardeli (Departemen Kimia FMIPA UNP, 2024)
Silica gel is one type of silica that can be used as an adsorbent. Silica gel has the ability to adsorb ions because it has two active sides that can be modified, namely the silanol group and siloxane. Silica modification is carried out to increase the adsorption ability of ions, one of which is Zn2+. In modified silica used 4-amino-5-hydroxy-2,7-naphthalenedisulfonate compounds as modifiers. In binding silica with modifier compounds, glycidoxypropyltrimethoxysilane (GPTMS) is added as a connecting compound. The modified silica was characterized by Infra-red spectrometer (FTIR) which showed the presence of sulfonate functional groups at wave number 1501,11 cm-1. The results of Zn2+ ion absorption with batch method are analyzed with an Atomic Adsorption Spectrophotometer (AAS) and obtained optimum conditions at pH 6 with an adsorption capacity of 1.257 mg/g with an adsorption percentage of 85,12%, at a contact time of 45 minutes with an adsorption capacity of 1.310 mg/g with an adsorption percentage of 71,29% .